Effects of Tannase and Ultrasound Treatment on the Bioactive Compounds and Antioxidant Activity of Green Tea Extract - Xu, Xiao-Yu (Antioxidants (Basel), 2019)
The present study investigated the effects of tannase and ultrasound treatment on the bioactive compounds and antioxidant activity of green tea extract. The single-factor experiments and the response surface methodology were conducted to study the effects of parameters on antioxidant activity of green tea extract. The highest antioxidant activity was found under the optimal condition with the buffer solution pH value of 4.62, ultrasonic temperature of 44.12 °C, ultrasonic time of 12.17 min, tannase concentration of 1 mg/mL, and ultrasonic power of 360 W. Furthermore, phenolic profiles of the extracts were identified and quantified by high-performance liquid chromatography. Overall, it was found that tannase led to an increase in gallic acid and a decrease in epigallocatechin gallate, and ultrasounds could also enhance the efficiency of enzymatic reaction.